Study of growth kinetics of Antarctic bacterial community for biodegradation of waste canola oil - Mohd Zahri, Khadijah Nabilah; Zulkharnain, Azham; Gomez-Fuentes, Claudio; Sabri, Suriana; Ahmad, Siti Aqlima (Desalination Publications, 2021)
The growth of bacteria is an important aspect in the biodegradation of pollutants, including hydrocarbons, since hydrocarbon pollution has become an increasingly serious environmental problem in cold regions. The present study investigates factors, such as salinity, nitrogen, yeast extract and waste canola oil that caused inhibitory effect at high concentration on the growth of Antarctic bacterial community known as BS14. Kinetic parameters were calculated using models that consider the substrate’s inhibitory effect on bacterial growth; this includes Haldane, Aiba, Teissier and Yano and Koga models. The data were regressed and well-fitted with Teissier model in the inhibitory effect of salt, yeast extract and waste canola oil (WCO) concentrations of –89.908, –70.746 and –57.850, respectively, for the Akaike Information Criterion (AICc) values, whereas the nitrogen source was fitted with Aiba model with AICc value at –84.583. Maximum specific growth rate (µmax) for each factor exhibited various speeds in cell growth rate where the µmax for the inhibition of growth by salt, nitrogen, yeast extract and WCO were at 1.004, 0.131, 1.005 and 0.544 h–1, respectively. The growth rate of Antarctic bacterial community BS14 was evaluated through non-linear regression model and the concentrations of substrate inhibition were identified.